Cognitive Flexibility and Social Adaptability in Individuals with Borderline Personality Disorder - Hafiza Tayyba Rafique; Kiran Javed; Saira Majid; Abdul Aziz; Azra Jaan (Research Journal of Psychology, 2025)
The present study investigated the inter relationship between cognitive flexibility and social adaptability in persons with Borderline Personality Disorder (BPD). The Cognitive Flexibility Inventory (CFI), Social Functioning Questionnaire (SFQ), and Borderline Symptom List (BSL-23) were administered to 70 participants between the ages of 18–45 years. There was no correlation between cognitive flexibility and social adaptability. Despite this, a large positive correlation between social adaptability and severity of BPD symptoms was established, indicating that individuals with more severe symptoms can exhibit increased social responsiveness as a mechanism of coping. Gender differences were also noted: females displayed markedly higher social adaptability than males, whereas no significant difference in cognitive flexibility was established between genders. These results underscore the contradictory and multifaceted nature of social functioning among BPD patients, emphasizing the need for accounting for symptom severity and gender in designing interventions. There is a need for future studies to explore these dynamics longitudinally and across more heterogeneous samples.